SENSITIVITAS ETIS DAN PERTIMBANGAN MORAL MAHASISWA AKUNTANSI TERHADAP DILEMA BISNIS - Kiki Apriyana; Lisa Martiah Nila Puspita (Jurnal Akuntansi, 2018)
and perceived societal pressure) to the ethical sensitivity and moral judgments of accounting students andto prove the influence of the dimension of moral intensity to the moral judgments through ethical sensitivity. Thisstudy used four case scenarios to explain the impact of the dimension of moral intensity, such as passing ofcompany policies, approving of a questionable expense report, manipulating of company books, and extending ofquestionable credit, by using 85 samples of accounting students in University of Bengkulu. Primary data wereobtained from the result of the dissemination of the questionnaires. The testing of hypotesis in this study was usingmultiple regression analysis and hierarchical regression analysis. The result showed that perceived overall harmhas negative influence to the ethical sensitivity and moral judgements of accounting students, meanwhile perceivedsocietal pressure has positive influence to the ethical sensitivity and moral judgments of accounting students. Theresult also showed that the perceived overall harm and perceived societal pressure influence moral judgements ofaccounting students through ethical sensitivity.Key words: Ethical Sensitivity, Moral Judgments, Moral Intensity, Perceived Overall Harm, and PerceivedSocietal Pressure.